Knowledge, attitudes and practices of sharps waste disposal by diabetic patients in rural South Africa - Lihle Ziqubu; Dudu G. Sokhela; Sibusiso D. Gabela (South African Family Practice)
Background: Sharps waste is hazardous, and it should be disposed of in a proper manner, as it can contribute to transmission of diseases and create a negative impact on the environment. The aim of this investigation was to determine the knowledge, attitudes and practices regarding sharps waste disposal of diabetic patients who inject themselves at home in uMzinyathi District Municipality, a rural area in KwaZulu-Natal, South Africa.